The role of exercise on lipit profils of women with cardiovascular disease - Biçer, Yonca; Yavuzkir, Mustafa (My University, 2007)
As a multidiciplinary concept, exercise has an important role to control the stress in a new healthy life style and to prevent risk factors of coronary heart disease. Physical activity has been firstly used on treatment of heart diseases in the USA, England and other countries commonly. Heart diseases cause lots of problems from the point of view of death and permanent impairment in Turkey and all of the world. Inefficient exercise has increased the cardio-vascular risk, and sedentary life complicates efficient management of blood glucose, cholesterol and blood pressure levels. On the contrary, systematic exercise has decreased the coronary artery disease risk. It has been accepted that physical activity effects positively lipid and lipoprotein profils. Systematic aerobic exercises improves cardiovascular autonomic control and the functional capacity. As a conclusion, the incidences of many coronary and cardio-vascular diseases decrease during lifetime. Physical capacity of individuals and rehabilitation programs should be evaluated from the point of view of positive effects of exercise. It is a clear fact that many positive effects occur with physical activity like improved myocardial perfusion, enhanced collateralisation, bettermentt of endothelial dysfunctions, prevention of formation of free radicals, increase in antioksidant enzim activity and decrease in the death rate from cardio-vascular morbidity and mortality.
Kalp damar hastali?i olan kadin hastalarin lipit profilleri üzerine düzenli egzersizin rolü
Keywords: antioxidant; cholesterol; free radical; glucose; lipid; lipoprotein; aerobic exercise; blood pressure; cardiovascular disease; cardiovascular risk; endothelial dysfunction; enzyme activity; functional status; glucose blood level; heart muscle perfusion; human; ischemic heart disease; lifestyle modification; medical assessment; medical education; morbidity; mortality; physical activity; prophylaxis; rehabilitation care; review; stress; turkey (bird); United States